Youtube e consciência histórica: algumas possibilidades de aplicação da plataforma na construção do saber histórico escolar - SANTOS, Cleidmar Avelar (2023)
The work carried out investigated the possibilities of using videos from the YouTube site in History classes. The driving problem was the passivity of students in the face of historical content displayed on the channels of this platform, not questioning the information acquired through this means and ignoring the factors that influence the production of these materials. Therefore, the objectives outlined were to analyze pre-selected YouTube videos with the clipping "Slavery and Black Resistance" aiming at their inclusion in the historical learning process, with greater reflection and scientific rigor, establishing a dialogue between the students' prior historical knowledge and the learned at school, enabling its application in practical life and expanding historical awareness, as proposed by Jorn Rüsen. The methodology took place in three phases: in the first, the selection and examination of the videos on the chosen theme were carried out, through criteria such as language, technical-methodological resources, among others, and the discourse analysis was carried out; in the second, a mixed questionnaire was applied on the research object and Focal Group debates were held on the defined theme. Finally, we proceeded to examine the data in light of the theoretical references of Didactics of History. From the results found, it was concluded that the use of YouTube for educational purposes has grown, demonstrating a didactic potential that offers a vast field to be explored by History teachers. Their videos can be leveraged at any stage of learning and build historical awareness by providing multiple narratives. They also favor the dialogue between the present and the past, the essence of historical knowledge. Easy to handle, second only to WhatsApp as the most accessed social network in the country. Based on these considerations, a product entitled “Using YouTube videos to bring a new look at black Slavery and Resistances” was formulated, didactic sequences with guidelines that seek to promote more dynamic History classes and in tune with the student reality.